Understanding contemporary India - Hill, Douglas; Cohen, Benjamin B.; Sridharan, Eswaran; Mukherji, Rahul; Zarhani, Seyed Hossein; Jaffrelot, Christophe; Bauman, Chad M.; Embree, Ainslie T.; Trivedi, Lisa; Alley, Kelly D. (Lynne Rienner Publishers, 2021)
Introducing India -- A geographic preface -- The historical context -- The political system -- Economies and development -- International relations -- The politics of caste -- Religion -- The status of women -- Population, urbanization, and environmental challenges -- Looking ahead.
Tabellen
Literaturangaben
Literaturhinweise Seite 293-315
Register Seite 319-334
"This third edition likewise includes six new chapters." (Preface, S. xv)
Keywords: India -- History -- 1947-; India -- Civilization -- 1947-; India -- Politics and government -- 1947-; India -- Social conditions -- 1947-; Aufsatzsammlung; Landeskunde; Indien